Penerapan Metode Discovery Untuk Meningkatkan Aktivitas Dan Hasil Belajar IPA Materi Organ-Organ Ekskresi Pada Manusia Dan Fungsinya pada Siswa SMPN 1 Praya Tengah - Surayah, Heny (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2024)
This type of research is classroom action research. Collecting data with observation techniques, tests and documentation. Data validation technique uses triangulation techniques. Data analysis used a qualitative descriptive technique. The results showed that the application of the discovery method was proven to increase student activity and learning outcomes. The increase in student activity in the initial study was only 9 students or 36%, rising to 15 students or 60% in the first cycle, and also 88% or 22 students in the second cycle, as well as increasing student learning outcomes and completeness from the average in the initial study only 59.20 rose to 65.20 in the first cycle, and 74.40 in the second cycle, with a learning completeness level of 7 students (28%) in the initial study, 56% or 14 students in the first cycle, 23 students or 92% stated complete learning and 2 students (8%) have not completed learning but all success criteria have been achieved so that the improvement process is declared complete in the second cycle.